2017
DOI: 10.1186/s12864-017-3610-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and signatures of selection in various goat breeds revealed by genome-wide SNP markers

Abstract: BackgroundThe detection of signatures of selection has the potential to elucidate the identities of genes and mutations associated with phenotypic traits important for livestock species. It is also very relevant to investigate the levels of genetic diversity of a population, as genetic diversity represents the raw material essential for breeding and has practical implications for implementation of genomic selection. A total of 1151 animals from nine goat populations selected for different breeding goals and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
4
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 86 publications
11
129
4
14
Order By: Relevance
“…The practical aspect of these population genomics studies lies on the possibility of detecting selected genes associated with traits of economic interest and acts as complement to gene mapping approaches (e.g., genomewide association studies [GWAS]) that may help to further genetically improve these traits on domestic species (Qanbari & Simianer, ). Furthermore, this knowledge is important from an evolutionary perspective by highlighting traits that have been exposed to natural and artificial selection as well as using this information to design and/or update breeding programs for conservation purposes worldwide (Brito et al., ; Cesconeto et al., ; Zhao, McParland, Kearney, Lixin, & Berry, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practical aspect of these population genomics studies lies on the possibility of detecting selected genes associated with traits of economic interest and acts as complement to gene mapping approaches (e.g., genomewide association studies [GWAS]) that may help to further genetically improve these traits on domestic species (Qanbari & Simianer, ). Furthermore, this knowledge is important from an evolutionary perspective by highlighting traits that have been exposed to natural and artificial selection as well as using this information to design and/or update breeding programs for conservation purposes worldwide (Brito et al., ; Cesconeto et al., ; Zhao, McParland, Kearney, Lixin, & Berry, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this knowledge is important from an evolutionary perspective by highlighting traits that have been exposed to natural and artificial selection as well as using this information to design and/ or update breeding programs for conservation purposes worldwide (Brito et al, 2017;Cesconeto et al, 2017;Zhao, McParland, Kearney, Lixin, & Berry, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only one genomic region located on chromosome BTA11 was overlapped on the ROH islands and shared by the two populations, probably because of the recent divergence between the two lineages (dairy and beef), with ancestral segments of the breed remaining on chromosome 11. This may indicate a strong selection for different traits such as beef and milk production (Brito et al, ). Maiorano et al () studied the same populations (Bp and Dp) and demonstrated proximity between these populations indicated by the low fixation index (Fst = 0.003), as they belong to the same breed and originated from the same ancestral population.…”
Section: Discussionmentioning
confidence: 99%
“…Natural selection plays an important role in determining the individuals that are best adapted to novel and existing environmental conditions. Besides natural selection, artificial selection has been widely applied to livestock species to achieve more desirable/profitable phenotypes [1]. For instance, sheep (Ovis aries) have been selected since domestication, approximately 9,000 years ago [2].…”
Section: Introductionmentioning
confidence: 99%